Becoming more attractive: Optimizing dead-end plant performance against spotted wing drosophila (Drosophila suzukii) - Sophie Wenz; Martin Meyer; Annette Reineke; Christine Becker (Crop Protection, 2026)

Biochar dominated the combined effect of silicate rock powder and biochar application on extracellular enzyme kinetics and nutrient dynamics in a sandy soil - Maria Ansari; Svenja Stock; Michaela A. Dippold; Susanne E. Hamburger; Claudia I. Kammann; Johannes Meyer zu Drewer; Nikolas Hagemann; Annette Eschenbach; Joscha N. Becker (Soil and Tillage Research, 2026)

Ecotonal gradients shape biodiversity of multiple estuarine taxa - Rebecca Oester; Benjamin Branoff; Johanna Biederbick; Luise Grüterich; Raphael Koll; Fay Lexmond; Nele Martens; Julian Mittmann-Goesele; Friederike Neiske; Widhi Putri; Sina Remmers; Diana Richter; et al. (Estuarine, Coastal and Shelf Science, 2026)

Mulching, rhizobial inoculation, and water supply shape soil enzyme activities and nutrient dynamics in a Namibian sandy soil under cowpea cultivation - Elisa Karina Albrecht; Simran Sekhri; Barbara Reinhold-Hurek; Shanmugam Solaiyappan Mani; Svenja C. Stock; Michaela A. Dippold; Annette Eschenbach; Joscha N. Becker (Plant and Soil, 2026)
Background and aims Agricultural soils in semi-arid sub-Saharan Africa are often low in soil organic carbon (SOC) and nitrogen (N), making them vulnerable to degradation and threatening food security of smallholder farmers. Conservation agriculture practices such as mulching are promoted as climate-resilient strategies to improve soil fertility, but it remains unclear whether these practices improve soil biogeochemical properties in semi-arid regions. Methods We conducted a greenhouse experiment that simulated a cowpea ( Vigna unguiculata ) growth period, a regional key crop, under water optimum and stress conditions using sandy soil from the Omusati region in Namibia. Effects of different mulches (wheat straw, wood chips, 1:1 mixture), inoculation with a locally adapted Bradyrhizobium and water conditions on soil biogeochemical properties, including SOC, N, microbial biomass and enzyme kinetics (β-glucosidase, chitinase, leucine-aminopeptidase) were investigated. Results We showed that mulching had limited short-term effects on SOC and N. Inoculation with rhizobia increased soil N, lowered C:N ratios and reduced N-related enzyme activities, demonstrating its potential to mitigate N limitation. Water stress decreased enzyme activities by 64%, indicating that water availability may outweigh management effects. Inoculation shifted the microbial demand from N towards C under water optimum, whereas all soils were N limited under water stress, reflected in enzymatic C:N ratios. Conclusion Our findings highlight cowpea inoculation as an effective strategy to improve soil N, while mulching provides additional benefits for soil fertility only under favourable water conditions. Increased C and N contents show that combining inoculated legumes with mulching can enhance nutrient availability in semi-arid agroecosystems, contributing to sustainable land management.

Rock-enhanced biochar exhibits similar priming effect as pure biochar application while improving short-term carbon stabilization in agricultural soils - Maria Ansari; Annemarie Lübeck; Johannes Meyer zu Drewer; Nikolas Hagemann; Annette Eschenbach; Joscha N. Becker (Biology and Fertility of Soils, 2026)
Combined application of biochar and silicate rock powder might have synergistic effects on carbon dioxide removal and soil improvement. However, it remains unknown how their combination affects mineralization and stabilization of soil organic carbon (SOC). We compared pure 13 C-labeled wheat-straw biochar, pure basanite rock powder, their co-application, and rock-enhanced biochar from co-pyrolysis of wheat and basanite. All amendments were mixed with three agricultural topsoils (temperate silty, temperate sandy, tropical sandy) and incubated for 66 days. The δ 13 C-signal of the respired CO 2 was monitored to determine amendment-induced priming of native SOC. After incubation, a density fractionation was conducted to investigate the potential stabilization of native and biochar-derived SOC as free particulate organic matter (fPOM), occluded POM (oPOM), and mineral-associated organic matter (MAOM). Pure basanite application did not influence short-term SOC dynamics, probably due to limited weathering within the 66-day incubation. In combined applications (co-application and rock-enhanced biochar), the biochar effect was dominant. The effects of biochar-containing amendments (biochar, co-application, and rock-enhanced biochar) were mainly controlled by texture and pH. The sandy soils exhibited positive priming following the application of biochar-containing amendments. In the temperate soils, positive priming occurred in MAOM, while native fPOM was partly shifted to oPOM. Input of biochar-derived SOC compensated losses of native SOC in fPOM and MAOM, resulting in overall SOC gains in most fractions. While priming intensity of all biochar-containing amendments was comparable, rock-enhanced biochar most strongly increased SOC in the density fraction interpreted as MAOM and had a higher short-term stability. These findings demonstrate that short-term effects of combined applications on SOC dynamics were dominated by the biochar component, while highlighting the potential of co-pyrolysis for short-term SOC stabilization.

Water vapor from deep soil reservoirs as a viable water source for plants in sandy soils - Simran Sekhri; Volker Kleinschmidt; Annette Eschenbach; Joscha N. Becker (Soil and Tillage Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Volatile Emission of Pear Tree (Pyrus communis) and Olfactory Perception of Pear Psyllids (Cacopsylla pyri and C. pyrisuga) are Affected by Elevated Tropospheric Ozone Concentration - Alicia Koßmann; Jannicke Gallinger; Margit Rid-Moneta; Christine Becker; Annette Reineke; Jürgen Gross (Journal of Chemical Ecology, 2025)
Climate change and rising tropospheric ozone concentration are impacting ecosystems in various ways and can influence the volatile-mediated interactions between insects and their host plants. In this study, individuals of the psyllid species Cacopsylla pyri and C. pyrisuga as well as their host plant Pyrus communis were exposed to elevated but naturally occurring ozone concentrations. The effects on the olfactory perception of the insects and the volatile emission of the plants were examined. Ozone exposure affected the olfactory perception of C. pyri and C. pyrisuga. While the perception threshold of hexanal increased in C. pyri , the perception of the tested compounds was not impaired in C. pyrisuga . Behavioural tests with ozone exposed C. pyri revealed an unchanged repellent effect of nonanal, while hexanal and a synthetic volatile blend became repellent to this species. These findings show only minimal direct effects of moderate ozone concentrations on olfactory perception of pear psyllids. In contrast, chemical analysis of the host plant odours showed a dramatic change in the volatile composition during ozone exposure, with a statistically significant decrease of terpenes and an increase of aldehydes and ketones, showing a greater impact of ozone on the emitter than on the receiver in the pear-psyllid system. This study highlights that moderate ozone levels can alter volatile emissions, potentially disrupting host plant location and impacting other insect–plant interactions that depend specifically on volatile-mediated communication.

Change Your Diet: How CO 2 , Plant Phenology and Genotype Alter Grapevine Quality and Affect Performance and Larval Transcriptome of an Insect Herbivore - Christine Becker; Christof B. Steingass; Heiko Vogel; Annette Reineke (Molecular Ecology, 2025)
Herbivorous insects need to cope with changing host plant biochemistry caused by abiotic and biotic impacts, to meet their dietary requirements. Larvae of the multivoltine European grapevine moth Lobesia botrana , one of the main insect pests in viticulture, feed on both flowers and berries. The nutritional value and defence compounds of these organs are changing with plant phenology and are affected by climate change which may accordingly alter plant–insect interactions. Here, we assessed the impacts of future elevated atmospheric CO 2 concentrations on the host plant quality of different grapevine organs and the larval performance and the transcriptome of L. botrana . Using the Geisenheim VineyardFACE facility, where ‘Riesling’ and ‘Cabernet Sauvignon’ were cultivated in the field under ambient or elevated (ca. + 20%) atmospheric CO 2 concentrations, we found that nutrient (amino acids and sugars) and defence compound (phenolic compounds) concentrations of inflorescences and ripening berries differed strongly due to plant phenology and less due to cultivar and CO 2 concentration. Assessing global gene expression after feeding on the respective organs, we found that larval transcriptomic plasticity largely mirrored the plant biochemical plasticity. Larval relative growth rate differed between treatments in a plant phenology‐dependent manner. Grape berries contained higher amino acid concentrations and altered phenolics profiles after larval feeding. In the near future, the grapevine– L. botrana interaction will probably change less because of elevated CO 2 concentrations than it does currently during one season. Changes associated with plant phenology, however, may be relevant for contemporary pest management.

Sexual reproduction in land plants: an evolutionary perspective - Annette Becker; Xia Chen; Thomas Dresselhaus; Nora Gutsche; Stefanie J. Müller-Schüssele; Stefanie Sprunck; Günter Theißen; Sophie de Vries; Sabine Zachgo (Plant Reproduction, 2025)
Key message We link key aspects of land plant reproductive evolution and detail how successive molecular changes leading to novel tissues and organs require co-evolution of communication systems between tissues. Abstract The transition of water-dependent reproduction of algae to mechanisms with very limited water dependence in many land plant lineages allowed plants to colonize diverse terrestrial environments, leading to the vast variety of extant plant species. The emergence of modified cell types, novel tissues, and organs enabled this transition; their origin is associated with the co-evolution of novel or adapted molecular communication systems and gene regulatory networks. In the light of an increasing number of genome sequences in combination with the establishment of novel genetic model organisms from diverse green plant lineages, our knowledge and understanding about the origin and evolution of individual traits that arose in a concerted way increases steadily. For example, novel members of gene families in signaling pathways emerged for communication between gametes and gametophytes with additional tissues surrounding the gametes. Here, we provide a comprehensive overview on the origin and evolution of reproductive novelties such as pollen grains, immobile sperms, ovules and seeds, carpels, gamete/gametophytic communication systems, double fertilization, and the molecular mechanisms that have arisen anew or have been co-opted during evolution, including but not limited to the incorporation of phytohormones, reactive oxygen species and redox signaling as well as small RNAs in regulatory modules that contributed to the evolution of land plant sexual reproduction.

Litter decomposition and prokaryotic decomposer communities along estuarine gradients - Friederike Neiske; Luise Grüterich; Annette Eschenbach; Monica Wilson; Wolfgang R. Streit; Kai Jensen; Joscha N. Becker (Soil Biology and Biochemistry, 2025)

Analysis of the extremely diverse local Moroccan almond cultivars provides essential resources for conservation and breeding - Souhayla Kodad; Christina M. Müller; Mohammad Jawarneh; Annette Becker; Moritz Sanne; Alexander Pfriem; Ahmed Elamrani; Aatika Mihamou; Malika Abid (Genetic Resources and Crop Evolution, 2025)

A land plant phylogenetic framework for GLABROUS INFLORESCENCE STEMS (GIS), SUPERMAN, JAGGED and allies plus their TOPLESS co-repressor - Clemens Roessner; Sven Griep; Annette Becker (Molecular Phylogenetics and Evolution, 2024)

Genome of Argania spinosa L.: insights into oil production and the tocopherol biosynthesis pathway - Oliver Rupp; Clemens Roessner; Naemi Lederer-Ponzer; Tassilo Erik Wollenweber; Annette Becker; Mouna Lamaoui (Genetic Resources and Crop Evolution, 2024)
Argan ( Argania spinosa L.) is a highly valued tree for its multiple uses as food and feed and for being linked to a broad range of benefits of pharmaceutical and cosmetic relevance. This multipurpose resource is becoming increasingly overused, which may disrupt the whole ecosystem’s sustainability. Due to the high socio-economic status of this tree, research interventions are needed to reverse the forest regressive trend, restore the disturbed ecosystem, and conserve genetic diversity. However, research on argan is restricted by the lack of accessible information on the genetic and genomic bases of the species, specifically a functional annotated genome. Herein, we report the reference transcriptome aided annotation of the argan tree genome using de novo gene prediction programs aided by homology information from different plants. The results of the genome annotation using AUGUSTUS were subsequently improved by performing RNA sequencing. A total of 62,590 gene loci could be identified with 82,286 isoforms and a BUSCO completeness of 91.7%. To gain insight into the agronomically important compounds in argan oil, a comparative genome analysis and ortholog identification was performed, followed by phylogenetic tree construction of the main biosynthesis genes. Among those are fatty acids and tocopherols, the latter being the main factor behind the increasing demands for argan oil. Our analysis is the initial step to provide breeders, geneticists, and the industries with adequate genomic information, facilitate improvement of economically important traits and to selectively adapt the tree to the increasing impact of climate change.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Effects of cowpea (Vigna unguiculata) inoculation on nodule development and rhizosphere carbon and nitrogen content under simulated drought - Joscha N. Becker; Janis Grozinger; Abhijit Sarkar; Barbara Reinhold-Hurek; Annette Eschenbach (Plant and Soil, 2024)
Aims Inoculation with climate-adapted rhizobia is able to increase legume productivity in drought-prone regions of Sub-Saharan Africa. Enhanced nodulation might additionally affect plant-soil interactions and control rhizosphere carbon (C) and nitrogen (N) pools. Methods We investigated inoculation effects on nodulation and biological N 2 fixation (BNF) of Vigna unguiculata and consequent effects on C and N pools in two Namibian soils. Three treatments ( Bradyrhizobium sp.1–7 inoculant, non-inoculated, N-fertilised with 50 kg N ha −1 ) were applied in rhizoboxes at 45% and 20% maximum water holding capacity. Nodule development was photo-documented, and rhizobia-DNA sequences were identified. BNF was assessed by δ 15 N enrichment, and organic C and N pools were analysed in bulk and root adherent soil. Results Plant growth initially enhanced mineral N losses from the rhizosphere at flowering stage (6 weeks growth), but led to a re-increase of N, and organic C contents after ripening (10 weeks). Inoculation had no effect on nodulation and soil C and N pools, indicating that both soils contained sufficient indigenous rhizobia to allow effective nodulation. However, the inoculant strain was more competitive in establishing itself in the root nodules, depending on the local conditions, showing a need for regional adjustment of inoculation strategies. Conclusion Water stress was the main limitation for nodulation and, in combination with soil type, substantially affected rhizosphere and bulk soil C and N contents. The temporally enhanced rhizodeposition after ripening could be able to maintain soil C and N pools after legume cultivation.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Are active and former floodplain soils of the lower middle Elbe similar? A study of soil characteristics and possible implications for forest restoration - Lizeth K. Vásconez Navas; Joscha N. Becker; Adrian Heger; Alexander Gröngröft; Annette Eschenbach (CATENA, 2023)

Biological control in a changing climate: plant-mediated impact of elevated CO2 concentration on Lobesia botrana eggs and egg parasitism by Trichogramma cacoeciae - Christine Becker; Katharina Herrmann; Annette Reineke (Journal of Pest Science, 2023)
Climate change can affect biological pest control by altering trophic interactions. Elevated carbon dioxide (CO 2 ) concentrations can reduce host plant quality and, in turn, alter herbivore and natural enemy preference and performance. Using the Geisenheim VineyardFACE (free-air carbon dioxide enrichment) facility, we studied plant- and herbivore-mediated bottom-up effects of elevated CO 2 concentration on the European grapevine moth, Lobesia botrana , and the parasitoid Trichogramma cacoeciae . Grapevine inflorescences of two cultivars cultivated at ambient or elevated CO 2 (aCO 2 and eCO 2 : 400 and 480 ppm) in the VineyardFACE were incorporated into L. botrana artificial diet. Eggs laid by the respective adults were parasitized by T. cacoeciae . Egg size and emergence rate of L. botrana as well as parasitism rate, parasitoid emergence rate and egg size preference of T. cacoeciae were evaluated. We observed an indirect grapevine cultivar-dependent bottom-up effect of CO 2 on both herbivore and egg parasitoid. Compared to aCO 2 , eCO 2 resulted in larger host eggs and higher parasitism rates regarding Riesling-feeding but not regarding Cabernet Sauvignon-feeding L. botrana larvae. Parasitoid emergence rate was higher when L. botrana had fed on Riesling compared to Cabernet Sauvignon-diet. Egg size preference depended on the host’s diet: T. cacoeciae preferred larger L. botrana eggs when the larvae had fed on grapevine-containing diet but not when they fed on standard artificial diet. Our results highlight the importance of the host’s diet for the parasitoid’s preference and performance. They furthermore suggest that the future efficiency of L. botrana -biocontrol by T. cacoeciae will not decrease under elevated CO 2 concentrations.

Altered volatile emission of pear trees under elevated atmospheric CO2 levels has no relevance to pear psyllid host choice - Jannicke Gallinger; Margit Rid-Moneta; Christine Becker; Annette Reineke; Jürgen Gross (Environmental Science and Pollution Research, 2023)
The impact of climate change drivers on cultivated plants and pest insects has come into research focus. One of the most significant drivers is atmospheric carbon dioxide, which is converted into primary plant metabolites by photosynthesis. Increased atmospheric CO 2 concentrations therefore affect plant chemistry. The chemical composition of non-volatile and volatile organic compounds of plants is used by insects to locate and identify suitable host plants for feeding and reproduction. We investigated whether elevated CO 2 concentrations in the atmosphere affect the plant-pest interaction in a fruit crop of high economic importance in Europe. Therefore, potted pear trees were cultivated under specified CO 2 conditions in a Free-Air Carbon dioxide Enrichment (FACE) facility at Geisenheim University in Germany for up to 14 weeks, beginning from bud swelling. We compared emitted volatiles from these pear trees cultivated for 7 and 14 weeks under two different CO 2 levels (ambient: ca. 400 ppm and elevated: ca. 450 ppm CO 2 ) and their impact on pest insect behavior. In total, we detected and analyzed 76 VOCs from pear trees. While we did not detect an overall change in VOC compositions, the relative release of single compounds changed in response to CO 2 increase. Differences in VOC release were inconsistent over time (phenology stages) and between study years, indicating interactions with other climate parameters, such as temperature. Even though insect-plant interaction can rely on specific volatile compounds and specific mixtures of compounds, respectively, the changes of VOC patterns in our field study did not impact the host choice behavior of C. pyri females. In olfactometer trials, 64% and 60% of the females preferred the odor of pear trees cultivated under elevated CO 2 for 7 and 14 weeks, respectively, over the odor from pear trees cultivated under ambient CO 2 . In binary-choice oviposition assays, C. pyri females laid most eggs on pears during April 2020; on average, 51.9 (± 51.3) eggs were laid on pears cultivated under eCO 2 and 60.3 (± 48.7) eggs on aCO 2.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Towards a genetic model organism: an efficient method for stable genetic transformation of Eschscholzia californica (Ranunculales) - Dominik Lotz; Jafargholi Imani; Katrin Ehlers; Annette Becker (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)
California poppy ( Eschscholzia californica ) is a member of the Ranunculales, the sister order to all other eudicots and as such in a phylogenetically highly informative position. Ranunculales are known for their diverse floral morphologies and biosynthesis of many pharmaceutically relevant alkaloids. E. californica it is widely used as model system to study the conservation of flower developmental control genes. However, within the Ranunculales, options for stable genetic manipulations are rare and genetic model systems are thus difficult to establish. Here, we present a method for the efficient and stable genetic transformation via Agrobacterium tumefaciens -mediated transformation, somatic embryo induction, and regeneration of E. californica. Further, we provide a rapid method for protoplast isolation and transformation. This allows the study of gene functions in a single-cell and full plant context to enable gene function analysis and modification of alkaloid biosynthesis pathways by e.g., genome editing techniques providing important resources for the genetic model organism E. californica.

The prevention of musculoskeletal complaints: long-term effect of a work-related psychosocial coaching intervention compared to physiotherapy alone—a randomized controlled trial - Annette Becker; Peter Angerer; Jeannette Weber; Andreas Müller (International Archives of Occupational and Environmental Health, 2020)
Purpose Research shows that psychosocial factors play a significant role in the emergence of musculoskeletal complaints (MSC). The aim of this study was to determine the long-term effects on unspecific MSC by a combined physiotherapy and coaching intervention compared to physiotherapy alone. The coaching intervention focussed on enabling better strategies for coping with work stressors. Methods The participants of a previous randomized controlled intervention were invited to participate again in a third follow-up survey 22 months after the end of the intervention. In 2014, 65 nurses completed a 10-week personalised physiotherapy. Additionally, the intervention group ( n = 33) passed five individual coaching sessions, plus an opening and closing session. 44 nurses (IG: n = 24; CG: n = 20) passed again a physical examination as well as another questionnaire assessment in 2016. The primary outcome was MSC, secondary outcomes were work ability and work-related well-being. Due to missing data, multiple imputations were conducted using the mice package in R. Data were analysed by ANOVA with two-way repeated measures, t tests for independent samples and Chi-squared tests. Results In respect of MSC, stronger improvement of movement in the vertebral column was observed in the IG compared to the CG. No differences between the IG and CG regarding other long-term effects were observed. Conclusions The results suggest that the combined intervention of work-related coaching and physiotherapy had only a marginally stronger long-term effect with respect to MSC than physiotherapy alone.

Correction to: Lack of adverse effects in subchronic and chronic toxicity/carcinogenicity studies on the glyphosate-resistant genetically modified maize NK603 in Wistar Han RCC rats - Pablo Steinberg; Hilko van der Voet; Paul W. Goedhart; Gijs Kleter; Esther J. Kok; Maria Pla; Anna Nadal; Dagmar Zeljenková; Radka Aláčová; Júlia Babincová; Eva Rollerová; Soňa Jaďuďová; et al. (Archives of Toxicology, 2020)

Lack of adverse effects in subchronic and chronic toxicity/carcinogenicity studies on the glyphosate-resistant genetically modified maize NK603 in Wistar Han RCC rats - Pablo Steinberg; Hilko van der Voet; Paul W. Goedhart; Gijs Kleter; Esther J. Kok; Maria Pla; Anna Nadal; Dagmar Zeljenková; Radka Aláčová; Júlia Babincová; Eva Rollerová; Soňa Jaďuďová; et al. (Archives of Toxicology, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

The prevention of musculoskeletal complaints: a randomized controlled trial on additional effects of a work-related psychosocial coaching intervention compared to physiotherapy alone - Annette Becker; Peter Angerer; Andreas Müller (International Archives of Occupational and Environmental Health, 2017)

Water temperature increases in the river Rhine in response to climate change - Paulin Hardenbicker; Carsten Viergutz; Annette Becker; Volker Kirchesch; Enno Nilson; Helmut Fischer (Regional Environmental Change, 2017)

Arabidopsis flower development—of protein complexes, targets, and transport - Annette Becker; Katrin Ehlers (Protoplasma, 2016)

Influence of global change on phytoplankton and nutrient cycling in the Elbe River - Katrin Quiel; Annette Becker; Volker Kirchesch; Andreas Schöl; Helmut Fischer (Regional Environmental Change, 2011)

Heteroblasty—A Review - Gerhard Zotz; Kerstin Wilhelm; Annette Becker (The Botanical Review, 2011)

A comparative approach to the principal mechanisms of different memory systems - Ludger Rensing; Michael Koch; Annette Becker (The Science of Nature, 2009)

Decreased serum activity of semicarbazide-sensitive amine oxidase (SSAO) in patients treated with second generation antipsychotics: a link to impaired glucose metabolism? - Veit Roessner; Annette Weber; Andreas Becker; Georg Beck; Helge Frieling; Stefan Bleich (European Journal of Clinical Pharmacology, 2007)

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot - John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Laura M. Zahn; Lukas A. Mueller; Lena L. Landherr; Yi Hu; Daniel C. Ilut; Jennifer M. Arrington; Stephanie Choirean; Annette Becker; Dawn Field; et al. (Plant Molecular Biology, 2006)

A short history of MADS-box genes in plants - Günter Theissen; Annette Becker; Alexandra Di Rosa; Akira Kanno; Jan T. Kim; Thomas Münster; Kai-Uwe Winter; Heinz Saedler (Plant Molecular Biology, 2000)